Non-phytotoxic concentration and application interval of nemarioc-al phytonematicide in management of meloidogyne javanica on potato cultivar 'mondial G3' - Kobe, Selaelo Patrisia (My University, 2019)
Potato (Solanum tuberosum L.) is highly susceptible to root-knot (Meloidogyne species) nematodes, with no known nematode resistant genotypes. In Limpopo Province, two cucurbitacin-containing phytonematicides had been researched and developed. The active ingredients of the cucurbitacin-containing phytonematicides are cucurbitacins, which are allelochemicals that could induce phytotoxicity on crops being protected against nematode damage. The objectives of this study were to determine: (1) mean concentration stimulation point (MCSP) of Nemarioc-AL phytonematicide on potato cultivar ꞌMondial G3ꞌ for managing M. javanica and (2) application interval of Nemarioc AL phytonematicide on potato cultivar ꞌMondial G3ꞌ. Sprouted tubers were planted in 10 cm deep/pot with each pot filled with steam-pasteurised soil and Hygromix at 3:1 (v/v) ratio in the field under microplot conditions. After 100% emergence (2 weeks), each plant was inoculated with 5 000 M. javanica eggs and second-stage juveniles (J2). Seven treatments, namely, 0, 2, 4, 8, 16, 32 and 64% Nemarioc-AL phytonematicide were arranged in a randomised complete block design, with 11 replications. In Objective 2, four treatments, namely, 1, 2, 3 and 4 weeks were arranged in randomised complete block design, with 15 replications. Plant variables and nutrient elements were subjected to the Curve-fitting Allelochemical Response Data (CARD) model to generate biological indices used to compute MCSP using the relation MCSP = Dm + Rh/2 and the overall sensitivity value (∑k). The MCSP for plant variables and nutrient elements, were empirically derived as 4.31% and 1.33%, with the ∑k of 18 and 4 units, respectively. Nematode variables and increasing concentrations of Nemarioc-AL phytonematicide exhibited negative quadratic relations where eggs, J2 in soil and roots and total population (Pf) were optimised at xv 14.43, 28.23, 23.30 and 13.55%. To conduct Objective 2 which is application interval, empirically derived MCSP value of 4.31% from Objective 1 was used. Application interval was optimised using the concept of 1, 2, 3, and 4 weeks in weeks-per-month-of-30-days. The application interval of 4.31% was established at 2.43 weeks which translated to 18 days [(2.43 weeks/4 weeks) × 30 days]. All nematode variables in Objective 2 were not significantly different at all intervals. In, conclusion Nemarioc-AL phytonematicide can be used at 4.31% concentration to control nematodes population densities without being phytotoxic to crops at 18 days application interval.
Thesis (M. A. Agriculture (Plant Protection)) -- University of Limpopo, 2019
Keywords: Root-knot nematodes; Phytonematicides; Potatoes; Nematocides; Root-knot nematodes; Plant nematodes -- Biological control